From Pen to Keyboard: A Qualitative Case Study on Nurses’ Experiences of Electronic Medical Record (EMR) Transition in a Long-Term Care Facility in the United Arab Emirates - Cariaso, Anroe Alan Cabra (Celebes Nursing Journal, 2025)
Introduction: This qualitative case study explored how nurses in a long-term care facility in the United Arab Emirates experienced the transition from paper-based documentation to an Electronic Medical Record system. As healthcare organizations increasingly adopt digital solutions, understanding nurses’ adaptation to technological change is essential for supporting effective documentation, communication, and patient care. Objective: The study aimed to describe nurses’ transition experiences, including perceived challenges, coping strategies, and the impact of the new system on their daily practice. Methods: Twenty-eight nurses participated in the study. Participants were first recruited through purposive sampling, and theoretical sampling was then used to include clinical nurse leads, a nurse informatics coordinator, and a director of clinical operations once initial themes emerged. Data were collected through semi-structured interviews and analyzed using conceptual and relational content analysis. Secondary institutional data, including system reports and audit findings, were integrated to provide additional contextual understanding. Results: Six themes captured the transition process, beginning with uncertainty and early system difficulties, followed by the development of coping strategies, changes in communication patterns, and recognition of improved documentation accuracy and long-term value. The integration of secondary data supported these themes, showing gradual improvements in system use and documentation quality over time. Conclusion: The study concludes that electronic medical record implementation in long-term care settings requires attention to technical readiness, emotional responses, and the social dynamics of change. Supportive training, leadership engagement, and continuous feedback processes are essential for achieving a smooth and sustainable transition.